Pengembangan Teori Pendidikan Islam Perspektif Muhammad Jawwad Ridla (Religius Konservatif, Religius Rasional, Pragmatis Instrumental) - Fajar Kurniawan (Institut Agama Islam Negeri Bengkulu, 2019)
Abstract: Development of Islamic Education Theory Perspective of Muhammad Jawwad Ridla (Conservative Religious, Rational Religious, Pragmatic Instrumental) This article discusses the study of the theory of Islamic education in the perspective of Muhammad Jawwad Ridla with six theories of Islamic Education built by Jawwad Ridla and Analysis of Jawwad Ridla concerning the three schools of Islamic education philosophy with the main characters who tend to these schools. The method of writing scientific papers uses library research. Namely, the author looks for data sources by prioritizing concepts and theories that refer to writing literature related to the specific research theme. The approach to writing scientific papers uses a philosophical approach. The results of this study are 1) The theory of Islamic education built by Muhammad Jawwad Ridla has several aspects, among them are the Concept of Teaching / Learning, Psychological Basics of the learning process, Understanding of student subjects, teaching methods, Teaching (teachers) and preparing individuals to participate active in the economic life of the community. 2) Muhammad Jawwad Ridla classifies the three main schools of Islamic education philosophy: 1) Conservative Religious Flow which is only covered by religious teachings. The main figures in this school are al-Ghazali, 2) Religious-rational, Ikhwan al-Shafa considers all disciplines as important with the flow they adhere to, 3) Pragmatic instrumentalism, adherents of this sect, Ibn Khaldun. He revealed that education is to gain worldly expertise and ukhrowi, both of which must provide benefits.Abstrak: Pengembangan Teori Pendidikan Islam Perspektif Muhammad Jawwad Ridla (Religius Konservatif, Religius Rasional, Pragmatis Instrumental). Artikel ini membahas tentang kajian teori pendidikan Islam dalam perspektif Muhammad Jawwad Ridla dengan enam teori Pendidikan Islam yang dibangun oleh Jawwad Ridla dan Analisis Jawwad Ridla mengenai tiga aliran filsafat pendidikan Islam dengan tokoh utama yang berkecenderungan ke aliran-aliran tersebut. Metode penelitian karya ilmiah ini menggunakan kajian pustaka (library research). Yaitu penulis mencari sumber data dengan mengedepankan konsep dan teori yang mengacu pada literatur-literatur kepenulisan terkait dengan tema penelitian secara spesifik. Adapun pendekatan penulisan karya ilmiah ini menggunakan pendekatan filosofis. Hasil penelitian ini yaitu 1) Teori pendidikan Islam yang dibangun oleh Muhammad Jawwad Ridla terdapat beberapa aspek yaitu diantaranya adalah Konsep Pengajaran/Pembelajaran, Dasar-dasar psikologis proses pembelajaran, Pemahaman tentang subjek didik, metode pengajaran, Ppengajaran (guru) dan penyiapan individu untuk berpartisipasi aktif dalam kehidupan ekonomi masyarakat. 2) Muhammad Jawwad Ridla mengklasifikasikan tiga aliran utama filsafat pendidikan Islam : 1) Aliran Religius Konservatif yang hanya dilingkupkan pada ajaran keagamaan saja. Tokoh utama pada aliran ini yakni al-Ghazali, 2) Religius-rasional, Ikhwan al-Shafa menganggap semua disiplin ilmu adalah penting dengan aliran yang dianutnya, 3) Aliran pragmatis instrumental, penganut aliran ini yakni Ibnu Khaldun. Beliau mengungkapkan pendidikan adalah untuk mendapatkan keahlian duniawi dan ukhrowi, keduanya harus memberikan keuntungan.